The local expression and trafficking of tyrosine hydroxylase mRNA in the axons of sympathetic neurons - Gervasi, Noreen M. (RNA, 2016)
Synthesis and regulation of catecholamine neurotransmitters in the central nervous system are implicated in the pathogenesis of a number of neuropsychiatric disorders. To identify factors that regulate the presynaptic synthesis of catecholamines, we tested the hypothesis that the rate-limiting enzyme of the catecholamine biosynthetic pathway, tyrosine hydroxylase (TH), is locally synthesized in axons and presynaptic nerve terminals of noradrenergic neurons. To isolate pure axonal mRNA and protein, rat superior cervical ganglion sympathetic neurons were cultured in compartmentalized Campenot chambers. qRT-PCR and RNA in situ hybridization analyses showed that TH mRNA is present in distal axons. Colocalization experiments with nerve terminal marker proteins suggested that both TH mRNA and protein localize in regions of the axon that resemble nerve terminals (i.e., synaptic boutons). Analysis of polysome-bound RNA showed that TH mRNA is present in polysomes isolated from distal axons. Metabolic labeling of axonally synthesized proteins labeled with the methionine analog, L-azidohomoalanine, showed that TH is locally synthesized in axons. Moreover, the local transfection and translation of exogenous TH mRNA into distal axons facilitated axonal dopamine synthesis. Finally, using chimeric td-Tomato-tagged constructs, we identified a sequence element within the TH 3′UTR that is required for the axonal localization of the reporter mRNA. Taken together, our results provide the first direct evidence that TH mRNA is trafficked to the axon and that the mRNA is locally translated. These findings raise the interesting possibility that the biosynthesis of the catecholamine neurotransmitters is locally regulated in the axon and/or presynaptic nerve terminal.